(untitled) (Historia, 2021)
The formation of the Union of South Africa in 1910 signified the emergence of a single political and economic entity from two predominantly British colonies and two British colonies with a predominantly white Afrikaner population. Economic progress based on the rationality of a single market constituted a powerful motive for the constitutional union. In promoting economic cooperation, markets were liberalised to allow the free movement of capital, labour and goods. The South African economy was largely a primary economy by 1910, dependent on agricultural and mining production for foreign exchange revenue. Domestic business linked to the mining sector created demand for small industrial enterprises and financial institutions. After the discovery of diamonds and gold in the last quarter of the nineteenth century, international interest in the South African economy exploded. Together with foreign mining entrepreneurs, exploration and digging activities gave rise to urban centres where business enterprises increased rapidly.